2010
DOI: 10.1111/j.1469-0691.2010.03177.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quorum sensing-dependent virulence factor production and its relationship with antimicrobial susceptibility in Pseudomonas aeruginosa respiratory isolates

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen causing severe respiratory infections. The pathogenesis of these infections is multifactorial and the production of many virulence factors is regulated by quorum sensing (QS), a cell-to-cell communication mechanism. The two well defined QS systems in P. aeruginosa, the las and rhl systems, rely on N-acyl homoserine lactone signal molecules, also termed autoinducers. We assessed the activity of QS-dependent virulence factors (including elastase, alkaline prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 26 publications
8
65
2
Order By: Relevance
“…In the light of the published genomic data, further support for the idea that the las system positively regulates the expression of both rhlR and rhlI have been defined [5]. Other studies reported the regulation of pyocyanin by QS previously [10,15,16]. It was also documented that pseudomonas strains can express increased pyocyanin levels despite decreased expressions in one or both QS systems.…”
Section: Discussionsupporting
confidence: 48%
“…In the light of the published genomic data, further support for the idea that the las system positively regulates the expression of both rhlR and rhlI have been defined [5]. Other studies reported the regulation of pyocyanin by QS previously [10,15,16]. It was also documented that pseudomonas strains can express increased pyocyanin levels despite decreased expressions in one or both QS systems.…”
Section: Discussionsupporting
confidence: 48%
“…It has been reported that QS controls the regulation of virulence and biofilm formation that are 1000-fold more resistant to antibiotics [1].…”
mentioning
confidence: 99%
“…Pseudomonas aeruginosa, an opportunistic pathogen causes infections in cystic fibrosis (CF), burns, wounds and pneumonia patients [1]. QS plays a major role in controlling the virulence of P. aeruginosa by regulating various virulence traits viz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study car ri ed out with cli ni cal spe ci mens, Ka ra tu na and Yagci no ted that even tho ugh QS had a key ro le in the res pi ra tory tract in fec ti ons ca u sed by P. ae ru gi no sa, the QS mu tant stra ins ha ving low sen si ti vity to an ti mic ro bi al agents might al so le ad to in fec ti on. 25 Ka ra man et al de ve lo ped pul mo nary in fec ti on mo del in rats by using PA O1 ve PA O JP2 (∆la sI/∆rhlI) re fe ren ce la bo ra tory stra ins with agar be ads met hod. 26 As a re sult of the qu an ti ta ti ve culti va ti on of bronc ho al ve o lar la va ge (BAL) and lung tis su es on the 14th day of the in fec ti on, re se arc hers re por ted a sig ni fi cant in cre a se in the bac te ri al count of the gro up in fec ted with wild-type stra ins com pa red to the gro up in fec ted with mu tant strains.…”
Section: Ex Pe Ri Men Tal Ani Mal Mo Dels In Un Ders Tan Ding Qs Systemmentioning
confidence: 99%